Strategi Kapabilias Relasional Bagi Lembaga Kesejahteraan Sosial di Kabupaten Garut: Penguatan Aspek Kolaborasi dan Kemitraan Lembaga - Enung Huripah; Ramli Ramli; Endah Dwi Winarni (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2021)
One of important problems in organizing social welfare for People with Social Welfare Issues (PMKS) in Indonesia is the governance of Social Welfare Institutions (LKS). Indeed, LKS is a part of the Social Welfare Resources (PSKS) in Indonesia, so it is called one of the spearheads for social welfare implementation. Unfortunately, LKS tend to be problematic both internally and externally. On the other hand, the Indonesian government also encourages LKS to be accredited. Thus, this study chooses the governance of LKS in Indonesia as a theme to study. In detail, this study discusses a strategy to strengthen LKS governance capacity in collaboration and partnership aspects. These two aspects are aligned with one of the priorities of the Indonesian government for LKS, namely network and coordination improvement in social welfare implementation. This study argues the proper strategy in strengthening the LKS governance capacity in collaboration and partnership aspects is the relational capability strategy. This study is a case study research with a qualitative approach on LKS in Garut Regency.